2003
DOI: 10.1016/s1470-0328(02)02907-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic myomectomy for fibroids penetrating the uterine cavity: is it a safe procedure?

Abstract: Objective The purpose of the study was to evaluate the post-operative course and follow up of women who had undergone laparoscopic removal of intramural fibroids penetrating the uterine cavity. Design Retrospective study.Setting Center for Reconstructive Pelvic Endosurgery, Italy.Population Thirty-four women with fibroids penetrating the uterine cavity. Methods Laparoscopic myomectomy.Main outcome measures Feasibility and safety of surgical technique, length of operation, blood loss, intraor post-operative com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 18 publications
(29 reference statements)
1
17
0
Order By: Relevance
“…Should the cave open even so, it is advisable to close the myoma bed in two layers and provide antibiotic treatment in the postoperative period. This circumstance does not affect the time of hospitalisation [7].…”
Section: Discussionmentioning
confidence: 89%
“…Should the cave open even so, it is advisable to close the myoma bed in two layers and provide antibiotic treatment in the postoperative period. This circumstance does not affect the time of hospitalisation [7].…”
Section: Discussionmentioning
confidence: 89%
“…Less important seems to be the risk of recurrent leiomyomas after laparoscopy. Previous studies have shown a higher risk of recurrence after laparoscopic myomectomy than after a traditional myomectomy, with a 33% recurrence risk at 27 months [21] ; however, more recent randomized clinical trials showed no significant difference [25,26] . The number of myomas and their size and location into the uterine wall are probably the most important risk factors for recurrence, whereas the surgical route most likely does not play a major role.…”
Section: Discussionmentioning
confidence: 91%
“…seracchioli et al (13) in their evaluation on laparoscopic myomectomy reported that the feasibility of laparoscopic myomectomy has definitely been demonstrated. Although no definitive criteria have been established, deep intramural fibroids reaching the uterine cavity may represent a contraindication to laparoscopic myomectomy, due to intraoperative bleeding and inadequate closure of the myometrium.…”
mentioning
confidence: 99%
“…some of the main concerns regarding laparoscopic myomectomy have been adequate reconstruction and healing of the uterine wall defect following myomectomy, and the possible resulting obstetric complications, including ability of the uterus to withstand pregnancy and labour, and high incidence of elective caesarean section (12). Many of the previous cases of uterine rupture in pregnant women following laparoscopic myomectomy occurred during second and third trimesters (28-36 weeks) (12,13). seracchioli et al advocated adequate tissue approximation, prevention of haematoma formation and limited use of electro coagulation as pointers towards a successful laparoscopic procedure (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation